Self-Efficacy in Instructional Technology Contexts (Springer International Publishing, 2018)
This edited volume contains reports of current research, and literature reviews of research, involving self-efficacy in various instructional technology contexts. Chapter represent international perspectives across the broad areas of K-12 education, higher education, teacher self-efficacy, and learner self-efficacy to capture a diverse cross section of research on these topics. The book includes reviews of existing literature and reports of new research, thus creating a comprehensive resource for researchers and designers interested in this general topic. A system of peer review was implemented to select the work that appears in the book from a collection of author-submitted chapter proposals. The book is especially relevant to students and researchers in educational technology, instructional technology, instructional design, learning sciences, and educational psychology.